Gipaga Asing Interactive Teaching Material for Geometry Learning: Bahan Ajar Interaktif Gipaga Asing untuk Pembelajaran Geometri - Maulida, Khurin In; Wardana, Mahardika Darmawan Kusuma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Interactive digital resources support engaging mathematics learning for elementary students. Specific Background: Existing printed materials often lack visual and multimedia elements needed to sustain attention while learning geometry. Knowledge Gap: Few studies describe mobile-based teaching materials that integrate videos, animations, and HOTS-oriented tasks for Grade 4 geometry topics. Aims: This article presents the development of Gipaga Asing, an interactive mobile learning material for area and perimeter concepts of squares, rectangles, and triangles. Results: The product features videos, images, drag-and-drop activities, structured guidance, and HOTS practice and evaluation tasks. Each component is designed to strengthen conceptual understanding and promote higher-order reasoning. Novelty: The material combines full multimedia elements with a complete learning sequence, including religious routines, national identity elements, collaborative tasks, and independent HOTS assessment. Implications: This product can serve as an alternative teaching material that supports teachers in delivering engaging, technology-based mathematics lessons for elementary students. Highlights• Multimedia-based geometry learning• Integrated HOTS activities• Mobile learning design Keywords: Interactive Teaching Material, HOTS, Mobile Learning, Elementary Mathematics, Geometry